Sr–Nd Isotopic Evidence from Lacustrine Sediments: A Novel Approach for Discriminating East Asian Monsoon and Westerly Signals - Xueyun Ma (14366304) (2025)
Sr, Nd isotope and εNd(0) values of Hurleg Lake HL18-3 core, surface lake sediments and Bayin River sediments in the Qaidam Basin.